CUL2 and STK11 as novel response-predictive genes for neoadjuvant radiochemotherapy in esophageal cancer. (August 2010) - Metzger, Ralf; Heukamp, Lukas; Drebber, Uta; Bollschweiler, Elfriede; Zander, Thomas; Hoelscher, Arnulf H; Warnecke-Eberz, Ute
Aims: Neoadjuvant treatment strategies have been developed to improve the survival of patients with locally advanced esophageal cancer. Since only patients with major histopathological response benefit from multimodality treatment, we profiled the genome of patients with esophageal cancer for markers indicating response or nonresponse.Patients and methods: Pretreatment biopsies of responding and nonresponding patients with locally advanced esophageal cancer, as well as the corresponding normal epithelium, were analyzed by human genome microarrays. Differential gene expression was associated with histomorphological tumor regression. Quantitative real-time reverse transcriptase-PCR was applied for verification of the predictive value of a panel of the identified marker genes, including 66 patients.Results: We detected differentially expressed candidate genes with regard to response and nonresponse to neoadjuvant radiochemotherapy. The response-predictive impact of the novel markers, CUL2 and STK11, was confirmed by the verification study including 66 patients. Whereas CUL2 mRNA expression levels of greater than 1.7 was predictive for major response (p = 0.02) in adeno- and squamous cell carcinoma, STK11 was predominantly response predictive for adenocarcinomas. Downregulation of CUL2 (p = 0.04) and STK11 (p = 0.02) mRNA also correlated with a more favorable prognosis.Conclusion: We identified two novel markers, CUL2 and STK11, for response prediction in esophageal cancer. They will be applied to complement our panel of response-predictive markers to further individualize therapy.